Mycolactone enhances the Ca2+ leak from endoplasmic reticulum by trapping Sec61 translocons in a Ca2+ permeable state. Issue 22 (26th November 2021) - Bhadra, Pratiti; Dos Santos, Scott; Gamayun, Igor; Pick, Tillman; Neumann, Clarissa; Ogbechi, Joy; Hall, Belinda S.; Zimmermann, Richard; Helms, Volkhard; Simmonds, Rachel E.; Cavalié, Adolfo
Abstract : The Mycobacterium ulcerans exotoxin, mycolactone, is an inhibitor of co-translational translocation via the Sec61 complex. Mycolactone has previously been shown to bind to, and alter the structure of the major translocon subunit Sec61α, and change its interaction with ribosome nascent chain complexes. In addition to its function in protein translocation into the ER, Sec61 also plays a key role in cellular Ca 2+ homeostasis, acting as a leak channel between the endoplasmic reticulum (ER) and cytosol. Here, we have analysed the effect of mycolactone on cytosolic and ER Ca 2+ levels using compartment-specific sensors. We also used molecular docking analysis to explore potential interaction sites for mycolactone on translocons in various states. These results show that mycolactone enhances the leak of Ca 2+ ions via the Sec61 translocon, resulting in a slow but substantial depletion of ER Ca 2+ . This leak was dependent on mycolactone binding to Sec61α because resistance mutations in this protein completely ablated the increase. Molecular docking supports the existence of a mycolactone-binding transient inhibited state preceding translocation and suggests mycolactone may also bind Sec61α in its idle state. We propose that delayed ribosomal release after translation termination and/or translocon 'breathing' during rapid transitions between the idle and intermediate-inhibited states allow for transient Ca 2+ leak, and mycolactone's stabilisation of the latter underpins the phenotype observed.